Intermediate journalistic cultures. International comparative studies in journalism (2013)
Defining journalistic culture is a complex process as it is necessary to explain on a general level the nature of culture is as a lifestyle. The attitudes of journalists are broadly embedded within meaning spheres that shape typical and traditional values of a common professional conduct. Throughout the last century, Western journalistic culture is taken as reference at all times to act as a model for imitation. However, this article presents the contextualization of different journalistic cultures as informative practice that currently varies from place to place and is determined by the different social, political, cultural and economic situation. The multiplicity-or multipolarity- in journalism, has led to the study of so-called intermediate journalistic cultures defined by having different features of the Western journalistic culture. Today, more than ever, those fragmented cultures mould and develop the static and mono-based standardization of all international journalistic features. The following study clarifies the singularities of journalistic cultures in different regions around the globe. It is a huge task, but necessary to underpin the theoretical notions of an important line of research born in recent decades: international comparative studies in journalism.